Strategi Dinas Pelayanan Pajak DKI Jakarta dalam menghadapi pengalihan Bea Perolehan Hak Atas Tanah Dan Bangunan menjadi pajak daerah - , Richard Sanjaya Manihuruk ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of Government appreciation to the implementation of regional autonomy is transfer of management of fees for acquisition of land and building (BPHTB) from central government to local government, provided that collection of BPHTB could be performed optimally and on the other hand service to the public does not decline. This study aims to examine the constraints faced and strategies need to be implemented by DKI Jakarta tax services office in overcoming obstacles that appear to be related to the transfer BPHTB becoming Local Tax. The design of this research is descriptive qualitative research, using data obtained from in-depth interviews of the Regulation and Tax Counseling field, Local Tax Information System field, Senior employees Secretary, and Employee of DKI Jakarta tax services office informants. Data analysis was performed by the public sector value chain approach and qualitative SWOT analysis. The study findings suggest that the obstacles faced by Jakarta Tax Office include Human Resources, sets of Information Technology, sets of Regulations, and work culture. To overcome these obstacles, the Jakarta Tax Office needs to finish BPHTB regulations and guidelines, increase the number of BPHTB human resources accordance with the required qualifications, and develop human resources competency training schedule required, increase the number of MoU with banks other than Bank DKI, and finalize the online system of integrated BPHTB online services which reach BPHTB service activities in the district UPP and service payments at the bank.